"Baby Jihad": Analyzing White Nationalist Fears of Changing Western Demographics. Issue 1 (16th June 2022) - Hodson, Margaret
Abstract : Many white nationalist thinkers have attempted to justify their anti-Muslim views by exploiting fears of "jihad" in various forms. Based on an analysis of alt-right sources, this article proposes a new category of "baby jihad, " or jihad via demography, which undergirds Islamophobia in the West. White nationalists who fear "baby jihad" point to demographic changes in fertility rates, age distribution, religious identification, and migration patterns to argue that Muslims pose an existential threat to Western society. This article places these arguments in context by citing demographic data and begins to explore some of the gendered dynamics associated with the politicization of reproduction. "Baby jihad" is a useful conceptual lens for understanding rising populism and anti-refugee sentiment throughout North America and Europe.